2021
DOI: 10.1117/1.jrs.15.048505
|View full text |Cite
|
Sign up to set email alerts
|

Variability of the snowline altitude in the eastern Tibetan Plateau from 1995 to 2016 using Google Earth Engine

Abstract: The glacier snowline can be used as an indicator of a glacier's equilibrium line, which is a pivotal parameter for studying the effect of climate change on glaciers. However, the relationship between snowline altitudes (SLAs) and climatic regime, as well as the comparison between different glacier types, has received less attention. Using Google Earth Engine, we first developed an automated algorithm that employs the Otsu thresholding method to distinguish snow-covered areas from clean ice on a near-infrared b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…The areas with snow decreasing are mainly in the Yangtze, Lancang River, Nujiang River, Yarlungzangbo, and Ganges, located in the southeastern and south part of the plateau. The gradual rise of the snowline height in these areas from 1995 to 2016 (Liu et al, 2021) also confirms the decreasing trend of snow cover. Areas of increasing and decreasing snow coexist in the Amu Darya, Indus, Tarim in the northwestern part of the plateau, and in the Qaidam and Yellow Rivers in the northeast.…”
Section: Contrasting Changes Of Snow Cover On the Tibetan Plateausupporting
confidence: 63%
“…The areas with snow decreasing are mainly in the Yangtze, Lancang River, Nujiang River, Yarlungzangbo, and Ganges, located in the southeastern and south part of the plateau. The gradual rise of the snowline height in these areas from 1995 to 2016 (Liu et al, 2021) also confirms the decreasing trend of snow cover. Areas of increasing and decreasing snow coexist in the Amu Darya, Indus, Tarim in the northwestern part of the plateau, and in the Qaidam and Yellow Rivers in the northeast.…”
Section: Contrasting Changes Of Snow Cover On the Tibetan Plateausupporting
confidence: 63%
“…Typically, a suite of images, often from Landsat satellites are paired with one or more Digital Elevation Models (DEMs) and a glacier outline from the beginning of the temporal scale of 75 interest (Li et al, 2022). From there, a variety of thresholds are evaluated and set for the area of interest with the SLA extracted from automated calculations to be used as the ELA (Racoviteanu et al, 2019) or manual tracing of outputs (Liu et al, 2021).…”
Section: Current Analysis Techniquesmentioning
confidence: 99%
“…Since routine ground-based measurements in a remote location such as south-central Peru are difficult to maintain, using satellite imagery to estimate the Equilibrium Line Altitude (ELA) has become a viable solution. Previous studies have shown 60 that the end of dry season (September) location of the snowline altitude (SLA) can act as a proxy for the ELA and ultimately be used to infer the mass balance of a glacier or ice cap (Fang et al, 2011;Hu et al, 2020;Liu et al, 2021;Racoviteanu et al, 2019). Here, we use a suite of imagery spanning 1985 to 2023 to assess the QIC at the end of the dry season through a cloudbased analysis of satellite imagery.…”
Section: Introductionmentioning
confidence: 99%
“…The OTSU thresholding method [60] is an adaptive technique used for image segmentation. In this study, it is used for distinguishing between ice and snow [61,62]. Moreover, this technique is well-suited for delimiting snowlines for a vast number of glaciers, in comparison to manual interpretation and semi-automated methods [63].…”
Section: Snow Mappingmentioning
confidence: 99%